Proportion of contextual effects in the treatment of fibromyalgia: A meta-analysis of randomised controlled trials - Nicola Whiteside; Aliya Sarmanova; Xi Chen; Kun Zou; Michael Doherty; Weiya Zhang; Natasya Abdullah (Springer, 2024)
Indexed by SCOPUS